Effects of Shenqi compound on intestinal microbial metabolites in patients with type 2 diabetes: A protocol for systematic review and meta analysis. Issue 48 (25th November 2020) - Xiong, Ran; Zhao, Changying; Zhong, Min; Zhang, Xinxia; Liu, Wanfu
Abstract: Introduction: According to the data from the 2017 Chinese Guidelines for the Prevention and Treatment of Type 2 Diabetes [Chin J Diabetes. 2017;20:81–117], [1] in 2013, the incidence of T2DM in China was 10.4%, while nearly 63% of the patients did not receive standard diagnosis. T2DM has become a serious public health problem in China and even in the world. Intestinal flora, as a research hotspot related to T2DM and other diseases in recent years, is a kind of microorganism with a large number in the human intestinal tract, which is considered as one of the important factors affecting the metabolism of the endocrine system and the human internal environment. In fact, many concepts of traditional Chinese medicine (TCM) coincide with modern research results of intestinal flora. In fact, TCM is also widely used to regulate intestinal flora disorders, and plays a very important role in restoring the dysfunctional intestinal flora [Hu et al. Drug Eval. 2013:8–10].[2] T2DM is a chronic systemic progressive disease. Studies [Wang et al. Tianjin Chin Med. 2007;24:507–508][3] have shown that even ideal blood glucose control cannot prevent the failure of islet cells [Wang et al. Tianjin Chin Med. 2007;24:507–508], [3] and how to restore the function and number of islet cells has naturally become the focus and difficulty of our current research. Studies have shown that the changes in the contents of intestinal microflora and their metabolites are closely related to the performance of T2DM such as hyperglycemia, insulin resistance, and restoration of islet function, and play an important role in pathophysiological mechanisms such as chronic inflammation of T2DM [Sun et al. Shi Zhen Chin Med. 2012;23:1434–1436].[4] It has been confirmed that Shenqi compound, a TCM, regulates intestinal flora of T2DM. However, due to the lack of evidence, there is no specific method or suggestion, it is necessary to make a systematic evaluation of Shenqi compound to provide effective evidence for further research. Methods and analysis: Electronic databases included PubMed, Embase, Cochrane Library, Web of Science, Nature, Science Online, WanFang China Biomedical Database, VIP Medical Information, China national Knowledge Infrastructure (CNKI). Main results: Endotoxin, short-chain fatty acid, bile acid, indole. Other results: low density lipoprotein (LDL), high density lipoprotein (HDL), triglyceride (TG), total serum cholesterol (TC). The data will be extracted independently by 2 researchers, and the risk of bias in the meta-analysis will be systematically evaluated according to the Cochrane handbook. All data analysis will be performed using the Data statistics software Review Manager V.5.3. And occupy V.12.0. Results: The results of this study will systematically evaluate the effectiveness and safety of Shenqi compound on the effects of intestinal flora metabolites in patients with type 2 diabetes. Conclusion: Through the systematic review of this study, the published evidence of the effect of Shenqi compound on intestinal flora metabolites in patients with type 2 diabetes was summarized to further guide its promotion and application. Ethics and communication: This study is a systematic review with findings based on published evidence and does not require erB review or consent. We plan to publish the results in a journal or conference report. Open science framework (OSF) registration number: September 29, 2020. osf.io/gb3m2.(https://osf.io/gb3m2 ).